Nicaragua : Fourth and Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Requests for Extension of the Arrangement, Rephasing of Access, and Waiver of Nonobservance of Performance of Criterion, and Financing Assurances Review-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Nicaragua. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Economic performance in Nicaragua has been better than envisaged; nonetheless, vulnerabilities remain and will be compounded by electoral uncertainties. The decision to use part of the strong revenue performance to lower the fiscal deficit is appropriate. Exchange-rate and monetary policy remain broadly adequate. Fiscal adjustment should set the stage for a strong program of fiscal consolidation following the elections. Continued vigilance in the financial sector will be critical. Improvement in reporting and monitoring of foreign aid flows and transparency is necessary.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet